Three different Ge environments in a new Sr5CuGe9O24 phase synthesized at high pressure and high temperature. Issue 5 (20th August 2020) - Klein, Holger; Kodjikian, Stéphanie; Philippe, Rémy; Ding, Lei; Colin, Claire V.; Darie, Céline; Bordet, Pierre
Abstract : The high‐pressure/high‐temperature phase Sr5 CuGe9 O24 was solved by low‐dose electron diffraction tomography and refined against powder X‐ray diffraction data. The Ge ions in this compound have three different coordination numbers. Abstract : In the framework of expanding the range of copper‐based compounds in the pyroxene family, we have synthesized at high pressure and high temperature a powder containing a mixture of a new phase with stoichiometry Sr5 CuGe9 O24 having two identified impurity phases. Electron crystallography showed that the new phase crystallizes in the monoclinic space group P 2/ c, with unit‐cell parameters a = 11.8 Å, b = 8.1 Å, c = 10.3 Å and β = 101.3°. We applied the recently developed low‐dose electron diffraction tomography method to solve the structure by direct methods. The obtained structure model contains all 9 independent cation positions and all 13 oxygen positions. A subsequent refinement against powder X‐ray diffraction data ascertained the high quality of the structure solution, in particular, the unusual structural arrangement that there are three different environments for Ge in this phase.